Childhood Biological Knowledge as Correlate of Secondary School Students’ Interest in Biology - Opara Mary Felicia; Nnabuife Uchechukwu Maryjane (MultiTech Publisher, 2024)
Childhood biological knowledge has been shown to be an important variable that affects children’s interest and understanding in biology later in life. However, in teaching and learning, most Nigerian teachers tend not associate students’ interest and understanding in biology to their childhood experiences. Hence, this study investigated childhood biological knowledge as correlate of secondary school students’ interest in biology. Two research questions and two hypotheses guided the study. The study was a correlational study and was conducted in Anambra State, Nigeria. The population of the study comprised 13, 109 biology students (5, 988 males and 7, 121 females) in 161 government owned co-educational schools, across six education zones in the State. The instruments for data collection were a researcher made Childhood Biological Knowledge Scale (CBKS) to measure childhood biological knowledge and Biology Interest Questionnaire (BIQ) to measure interest. Data analyzed using Pearson product moment correlation coefficient (Pearson r) showed that childhood biological knowledge had a low positive correlation with students' interest in biology r = 24 and a low positive correlation of r= 32 for female and r= 05 for male. Thus, students’ childhood biological knowledge increases their interest in biology over time not withstanding their gender. The study recommended among others that Biology teachers should be knowledgeable about their students' childhood biological knowledge to help them correct misconceptions that could lead to poor achievement.